Prognostic value of neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio on low-grade appendiceal mucinous neoplasm: A single tertiary hospital experience. Issue 6 (14th April 2022) - Kuan, Tai-Chuan; Liang, Wen-Yi; Lin, Chun-Chi; Lin, Hung-Hsin; Huang, Sheng-Chieh; Cheng, Ho-Shuan; Chang, Shih-Ching; Jiang, Jeng-Kai; Lan, Yuan-Tzu
Abstract : Background: Low-grade appendiceal mucinous neoplasm (LAMN) is a rare disease, which prognostic factors were difficult to evaluate. Inflammation markers, like neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR), were used as prognosticators for various cancers. This study aimed to investigate the prognostic value of pretreatment NLR and PLR on LAMN. Methods: From January 2000 to September 2018, there were 57 patients diagnosed with LAMN in Taipei Veterans General Hospital. Patients diagnosed with mucinous cystadenoma, mucinous tumor with uncertain malignant potential before 2010 were also included based on previous classification. Clinical and pathological data were collected. Patients were separated into high-NLR (NLR-H) and low-NLR (NLR-L) groups according to cutoff value of 3. Similarly, they were separated into high-PLR (PLR-H), and low-PLR (PLR-L) groups with cutoff value of 300. Overall survival (OS) and recurrence-free survival (RFS) were analyzed. Results: Among all patients, the median follow-up time was 42 months. Age, gender, clinical manifestations, type of surgery, and T stage were similar in different NLR and PLR groups. Both NLR-H and PLR-H groups had higher rate of M1 stage of diseases (22.7% vs 9.4%, p = 0.04; 57.1% vs 8.8%, p < 0.01, respectively). PLR-H group had more presence of pseudomyxoma peritonei (PMP) (57.1% vs 15.2%, p = 0.03). In univariate analysis, factors such as age, gender, tumor perforation, and operation did not have impact on OS nor RFS. On the other hand, M1b stage is the only significantly poor prognostic factor on RFS (hazard ratio, 57.96, 95% CI, 5.16-651.23, p < 0.01). Conclusion: Both NLR-H and PLR-H had more M1 stage of diseases, but they were not correlated to OS nor RFS. PLR-H group had higher rate of presence PMP. Nevertheless, patients with LAMN and cellular PMP (M1b stage) had a higher rate of recurrence, and other factors showed no statistical difference in OS nor RFS.